Henry Tazewell papers - Tazewell, Henry, 1753-1799.
Chiefly letters (1795-1798) written by Tazewell to John Ambler and Richard Cocke, together with letters to John Page and one from John Langdon, reflecting Tazewell's views on the presidential administrations of George Washington and John Adams. Topics include the election of John Adams, the prospect of war with France, and activities of the U.S. Congress. Also includes biographical information (1999 and undated) on Cocke and Tazewell.
In part, typewritten transcripts.
Jurist and U.S. senator from Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John, -- 1735-1826.; Ambler, John, -- 1762-1836 -- Correspondence; Cocke, Richard, -- 1748-1816 -- Correspondence; Langdon, John, -- 1741-1819 -- Correspondence; Page, John, -- 1744-1808 -- Correspondence; Washington, George, -- 1732-1799.; United States. -- Congress; Presidents -- United States -- Election -- 1796.; France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- Foreign relations -- 1789-1809.; United States -- Politics and government -- 1789-1797.; United States -- Politics and government -- 1797-1801.; Virginia -- Politics and government -- 1775-1865.; Jurists; Senators, U.S. Congress -- Virginia